Assessing the costs and benefits of US renewable portfolio standards. (26th September 2017) - Wiser, Ryan; Mai, Trieu; Millstein, Dev; Barbose, Galen; Bird, Lori; Heeter, Jenny; Keyser, David; Krishnan, Venkat; Macknick, Jordan
Abstract: Renewable portfolio standards (RPS) exist in 29 US states and the District of Columbia. This article summarizes the first national-level, integrated assessment of the future costs and benefits of existing RPS policies; the same metrics are evaluated under a second scenario in which widespread expansion of these policies is assumed to occur. Depending on assumptions about renewable energy technology advancement and natural gas prices, existing RPS policies increase electric system costs by as much as 31 billion, on a present-value basis over 2015−2050. The expanded renewable deployment scenario yields incremental costs that range from 23 billion to 194 billion, depending on the assumptions employed. The monetized value of improved air quality and reduced climate damages exceed these costs. Using central assumptions, existing RPS policies yield 97 billion in air-pollution health benefits and 161 billion in climate damage reductions. Under the expanded RPS case, health benefits total 558 billion and climate benefits equal 599 billion. These scenarios also yield benefits in the form of reduced water use. RPS programs are not likely to represent the most cost effective path towards achieving air quality and climate benefits. Nonetheless, the findings suggest that US RPS programs are, on a national basis, cost effective when considering externalities.